2020
DOI: 10.1016/j.ajhg.2020.01.019
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of DNA Methylation Episignatures for Diagnosis and Phenotype Correlations in 42 Mendelian Neurodevelopmental Disorders

Abstract: Genetic syndromes frequently present with overlapping clinical features and inconclusive or ambiguous genetic findings which can confound accurate diagnosis and clinical management. An expanding number of genetic syndromes have been shown to have unique genomic DNA methylation patterns (called ''episignatures''). Peripheral blood episignatures can be used for diagnostic testing as well as for the interpretation of ambiguous genetic test results. We present here an approach to episignature mapping in 42 genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
242
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 195 publications
(265 citation statements)
references
References 41 publications
4
242
2
Order By: Relevance
“…Here we replicated and expanded earlier findings [15][16][17] of DNA methylation changes in ADNP syndrome. The mechanisms leading to these methylation changes are still unknown.…”
supporting
confidence: 88%
“…Here we replicated and expanded earlier findings [15][16][17] of DNA methylation changes in ADNP syndrome. The mechanisms leading to these methylation changes are still unknown.…”
supporting
confidence: 88%
“…However, the direct role of this methylation alteration on the pathophysiology of many of these diseases still needs further investigation. Our group has previously identified epi-signatures that can be used to specifically diagnose subjects with a variety of neurodevelopmental conditions, including syndromes that may clinically overlap with PHMDS [ 22 ]. The use of DNA methylation signatures can help solve many clinically ambiguous cases presenting with a neurodevelopmental phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Genomic DNA methylation profiles in peripheral blood, referred to as DNA methylation epi-signatures, have been associated with many human traits, including age, sex and disease status [ 18 21 ]. More recently, we and others have reported evidence of highly sensitive and specific peripheral blood epi-signatures associated with genetic mutations in a growing number of genes and genetic syndromes associated with developmental delay/intellectual disabilities and multiple congenital anomalies [ 22 25 ]. In addition, microarray-based genomic DNA methylation assessment has enabled simultaneous detection of imprinted disorders and Fragile X syndrome, which is often within the spectrum of differential diagnoses of these neurodevelopmental syndromes [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…When these epigenetic changes are maintained throughout development and across cell-types, these so called 'episignatures' can be used as biomarkers for the diagnosis of NDDs using easily accessible tissues such as peripheral blood [89][90][91][92]. Indeed, several very recent studies have already showed the potential for using disease-specific episignatures as diagnostic tool for NDDs, including patients with a known diagnosis as well as patients carrying variants of unknown significance [93][94][95].…”
Section: Dna Methylationmentioning
confidence: 99%